Deterioration After Mild Traumatic Brain Injury: A Single-Center Experience With Cost Analysis - Chojak, Rafał; Koźba-Gosztyła, Marta; Pawłowski, Mateusz; Czapiga, Bogdan (Frontiers in Neurology, 2021)
Background: Most traumatic brain injuries (TBIs) are mild (GCS score of 13 to 15). Patients with mild TBI (mTBI) are generally in good condition. In some cases, a neurological deterioration (manifested by a drop of ≥1 point in GCS score) can occur and neurosurgical intervention (NI) may be needed. Because of that, these patients are frequently admitted to a hospital for observation. The aim of our study was to determine the number of patients with mTBI that deteriorate or need NI. We also considered an economic aspect of hospital admissions of these patients. Methods: The study group consisted of 186 adult patients admitted to the neurosurgical department due to mTBI. Patients were divided into three groups according to an initial GCS score. The occurrence of deterioration, need for NI, length of stay (LOS), cost of stay and occurrence of death were analyzed. Results: The deterioration was observed in 7 (3.76%) out of all cases. In 3 (1.61%) of them, the NI was needed. The average LOS was 7.96 days and it was closely linked with an initial GCS score (p<0.001). The total cost of stay of all patients included in this study was about 1 188 668 PLN (306 357 USD) Conclusion: The deterioration occurred in a small number of patients with mTBI, the need for NI was even less common. Hospitalization of these patients is expensive. Further studies with prognostic model helping decide on admission/discharge are necessary.